Women as concordia seekers in Ancient Rome: gender discourses and propaganda ideology (second-first centuries BC). - Vivas, Carmen María Ruiz (Women's History Review, 2024)
Concordia was a moral tool for the regulation of conflicts and the maintenance of order within the ancient Roman family. This paper focuses on the relationship that Roman ideology established between women and harmony, conceiving them as guarantors of peace. From a perspective of gender and peace research, gender discourses present in texts as well as in the images and legends of Roman coins from the end of the Republic (2nd-1st centuries BC) are analysed. The article aims to answer the questions of how women were made responsible for peace, the symbolic meanings and implications this had, as well as the possibilities for agency and recognition it offered them.